PENGEMBANGAN MEDIA PERMAINAN PAPAN MONOPOLI BERBASIS KARAKTER PEDULI SOSIAL PADA MUATAN MATERI IPS - Made Ayu Diah Permata Riskiani; I Gusti Agung Ayu Wulandari (Jurnal Pendidikan Dasar, 2022)
Teachers only use lecture method, lack of the cultivation of social caring character value in students, as well as lack of learning media that support the activities of the teaching and learning process in class became the reasons why researcher conducted a new innovation in the development of learning media which is more interesting for students, effective, and efficient in the utilization namely monopoly board game media. This research purpose is to determine the monopoly board game model design based on the social caring character in the Social Studies material content for grade IV students as well as to determine the eligibility of the monopoly board game media model based on the social caring character in the Social Studies material content for grade IV students. The research model used is ADDIE. The data collection is conducted by using interviews, observations and questionnaire techniques. Data analysis used quantitative descriptive and qualitative descriptive methods. This monopoly board game media is considered eligible based on the results of the learning content expert test 77,5% with good qualification, learning design expert test 93,75% with very good qualification, learning media expert test 96,15% with very good qualification, individual trial test 95,83% with very good qualification, and small group trial test 91,66% with good qualification. Based on the data analysis of the validation results obtained, it can be concluded that this Monopoly Board Game Media Based on Social Caring Character is eligible to be used as a learning media in the Social Studies Material Content for Grade IV Elementary School.